Voir à fleur de peau : la violence de l’accommodation. À propos de la performance « Accommodation » de Hantu (Itinera, 2017)
Accommodation by Hantu (Jean Delsaux and Pascale Weber) is a performance based on the Diderot essay Letter on the Blind for the Use of those who can see. Being founded on features of « accommodation » phenomena, my paper examines the transformation of the sensory perception produced on the performer Pascale Weber and the spectators by the dramatic and performative device, based on sense of impossibility or difficulty to see. Moreover, it analyses the image of the contemporary world in its search of an identity and the violent relationship with the “Other” to whom Accommodation refers.